Effects of emigration; can it be made a means of relieving distress? - Jordan, Thomas (Dublin Statistical Society, 1856)
Many, for instance, we all know, are now occasionally assisted in our towns by benevolent individuals or associations. How much more effective might not this relief be, if instead of being given in small sums, it were bestowed at once and with the special view of enabling its objects to take advantage of the offer of the Emigration Commissioners. One case relieved in this manner would be equivalent to several on any other principle. Mendicancy would not be encouraged. The intending emigrant would be put into the way of realising the glorious privilege of being independent; and, as we showed before, his fellow-countrymen, though not relieved directly by the same individual or association, would be so indirectly. In this manner there could be a thorough investigation into the eligibility of each person?an investigation much more efficient than can possibly be made by the Emigration Commissioners, whose transactions must necessarily be on a large scale. Another object, too, could be accomplished by this plan, which the Emigration Commissioners profess themselves unable at present to effect. Their object, they say, is not to consider how distress may be best relieved here, but how the most suitable persons for the colony may be procured. But by the system of benevolence now suggested, the other object also would be secured ? a proper selection would be made for the colony, at the same time that pauperism would effectually be removed.
Read May 19th, 1856
Keywords: Emigration; Poverty; Emigration Commission; Assisted passage; 314.15